Identidade e história: Belém do Grão-Pará como narrativa da nacionalidade - FIGUEIREDO, Elielson de Souza (Universidade Federal do Pará, 2011)
This work admits the allegory concept presented by Fredric Jameson as Possibility for reading speech of the history through Brazilian poetic speech, especially the Dalcidio Jurandirs novel, Belém do Grão-Pará. The beginning of the twentieth century is read through circumstances lived by the protagonist Alfredo, starting from his move from Cachoeira do Arari to Belém. Using the Marxist dialectic premises, little by little we analyzed the meaning of anthropophagi as sort of decisive political attitude to rupture with the idea of Brazilian culture submission front to the external cultures, specifically Europes. The new dimension given to the European vanguard in cultural and esthetic Brazilian means, as well the intellectual argument between the revolutionary sections of the national art and the academic eighteenth century tradition, were essentials to the statement of a very peculiar place to Brazilian literature in Latin-American and global context, especially. Alfredo's migration, central character in the play, from country-side to the city although he finds out a Belém ruined because of the economical climax of rubber exploitation, its read, allegorically as kind of crossing between the cosmopolitan way of national elites and the cultural roots which popular sections of the country-side are linked. Instruments of this historical debate between the elites and the people, were in the movies and newspapers, also mentioned by the novel. In a glance on post-modernity and the appearance of global society, under the tutelage of cultural industry, It insists on the possibility of a Brazilian national identity despite of strong differences among areas, social classes and ethnic.